2019
DOI: 10.3233/wor-182826
|View full text |Cite
|
Sign up to set email alerts
|

Accounting for context: Social enterprises and meaningful employment for people with mental illness

Abstract: BACKGROUND: Many people living with mental illness want paid work, but finding and maintaining mainstream employment remains challenging. In recent decades, social enterprises have emerged as one alternative site for paid employment. Existing research has examined the experiences of people with mental illness working in social enterprises, but less is known about the organizational character of these workplaces. OBJECTIVE: The objective of this paper is to develop a better understanding of social enterprises a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
34
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(40 citation statements)
references
References 31 publications
5
34
1
Order By: Relevance
“…While the majority of studies predominantly analyzed the work and health situation of target staff with mental disorders working in social firms or social enterprises [1,, three studies reported additional employment opportunities for people with learning, sensory, intellectual, or developmental disabilities; or those suffering from long-term unemployment [48][49][50]. Fourteen studies reported evidence gained from the target group itself [28,[30][31][32][33][34][35][36][37][38][39][40][41]46], nine studies considered a mixed sample (e.g., of employees, managers, or support staff/carers [1,29,[42][43][44][45]47,48,50]), and two studies consisted of a sample of non-disabled participants as key informants (executive directors or managers) [27,49]. Socio-demographic characteristics of the included studies indicated that most participants were male (51-93.75%), except in three studies [30,31,33] (not specified in nine studies [27,29,[41][42][43][44][45]49,50]).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…While the majority of studies predominantly analyzed the work and health situation of target staff with mental disorders working in social firms or social enterprises [1,, three studies reported additional employment opportunities for people with learning, sensory, intellectual, or developmental disabilities; or those suffering from long-term unemployment [48][49][50]. Fourteen studies reported evidence gained from the target group itself [28,[30][31][32][33][34][35][36][37][38][39][40][41]46], nine studies considered a mixed sample (e.g., of employees, managers, or support staff/carers [1,29,[42][43][44][45]47,48,50]), and two studies consisted of a sample of non-disabled participants as key informants (executive directors or managers) [27,49]. Socio-demographic characteristics of the included studies indicated that most participants were male (51-93.75%), except in three studies [30,31,33] (not specified in nine studies [27,29,[41][42][43][44][45]49,50]).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Fourteen studies reported evidence gained from the target group itself [28,[30][31][32][33][34][35][36][37][38][39][40][41]46], nine studies considered a mixed sample (e.g., of employees, managers, or support staff/carers [1,29,[42][43][44][45]47,48,50]), and two studies consisted of a sample of non-disabled participants as key informants (executive directors or managers) [27,49]. Socio-demographic characteristics of the included studies indicated that most participants were male (51-93.75%), except in three studies [30,31,33] (not specified in nine studies [27,29,[41][42][43][44][45]49,50]). The age of participants ranged between 35.5 (median [34]) and 48 years (mean [30]) [1,28,[30][31][32][33][34]…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations